Effect of Perna viridis on hematological parameter in rats / Nur Syazwani Ahamad Fadzil - Ahamad Fadzil, Nur Syazwani (2015)
Perna viridis has been used for many centuries to cure many diseases traditionally. It also contains nutrients that may help in increase hematological parameter, thus, Perna viridis has the potential to be used to boost blood parameter. The objective of this study is to quantity the amount of protein and determine the effect of Perna viridis on hematological parameter in rats. The sample was processed through the freeze drying process and the amount of protein was determined using Bradford assay. The tested dose was 7.0mg/ml protein/kg and 52.0mg/ml protein lkg and each dose was administrated orally to two different groups for three weeks and one control group, n=6. Cardiac puncture was performed in all rats for hematological analysis. The protein concentration in 10mg/ml of Perna viridis powder is 0.55 mg/ml. The hematological analysis reveals that lymphocyte percentage we increase significantly (P<0.05) between control and high dose group. Hemoglobin (HGB) concentration show increase in mean for the high dose group and low dose group compared to control group but not significantly. As for platelet count, there is a significant increase in low dose group (p<0.05) compare to the high dose group .. As a conclusion, it has proven that Perna viridis has the ability to increase the platelet count at the low dose concentration and has the ability to increase HBG at low dose and high dose of consumption.